2014
DOI: 10.1099/mic.0.075226-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotransferase protein EIIANtr interacts with SpoT, a key enzyme of the stringent response, in Ralstonia eutropha H16

Abstract: EIIANtr is a member of a truncated phosphotransferase (PTS) system that serves regulatory functions and exists in many Proteobacteria in addition to the sugar transport PTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…The assumption of a covalent modification such as phosphorylation would be in line with previous data. Karstens and coworkers previously showed that in R. eutropha, SpoT1 but not SpoT2 interacted with the nonphosphorylated form of the EIIA Ntr component of the PTS system (33). This indicates a possible phosphorylation cascade from the carbon source uptake system to SpoT1, which could, in turn, influence the activity of the PHB mobilization system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption of a covalent modification such as phosphorylation would be in line with previous data. Karstens and coworkers previously showed that in R. eutropha, SpoT1 but not SpoT2 interacted with the nonphosphorylated form of the EIIA Ntr component of the PTS system (33). This indicates a possible phosphorylation cascade from the carbon source uptake system to SpoT1, which could, in turn, influence the activity of the PHB mobilization system.…”
Section: Discussionmentioning
confidence: 99%
“…Support for a connection between PHB metabolism and the stringent response in R. eutropha was recently published in two reports in which the authors identified an interaction of the PTS protein EIIA Ntr with the ppGpp synthase/hydrolase SpoT1 (33) and showed that an EIIA Ntr knockout mutant accumulated substantially more PHB than the wild type (34). Furthermore, the North American authors of this study claimed in a previous study that a mutant (Re2411) with a deletion in the H16_A1337 gene (ΔspoT2) had completely lost the ability to accumulate PHB, pointing to an essential function of SpoT2 for PHB metabolism (24).…”
mentioning
confidence: 99%
“…Bacterial two-hybrid assays indicated that this interaction occurs only with the unphosphorylated form of EIIA Ntr (133). Interaction with EIIB components.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…However, it is noteworthy that regulation of K + transport by PTS Ntr as observed in E. coli is not necessarily conserved in other bacteria. For instance, interaction of EIIA Ntr and KdpD is also operative in Rhizobium leguminosarum but absent in Ralstonia eutropha , suggesting that PTS Ntr serves different functions in different species [Karstens et al, 2014;Prell et al, 2012].…”
Section: Eiiamentioning
confidence: 99%
“…According to current evidence, only nonphosphorylated EIIA Ntr is engaged in protein-protein interactions [Karstens et al, 2014;Lee et al, 2007;Lüttmann et al, 2009Lüttmann et al, , 2012Pflüger-Grau et al, 2011]. In contrast to the canonical EI, EI Ntr carries an additional GAF domain fused to its N-terminus [Reizer et al, 1996].…”
Section: Eiiamentioning
confidence: 99%